Kinematics research progress of swim-start on the new start block - Yang, F. (Physical Activity and Health, 2018)
The new starting block by Omega firstly appeared in Beijing Olympic Games since the FINA (Fédération Internationale de Natation) amended the rule (OSB11, Corgémont, Switzerland). And this new start block gave rise to the researchers and academics focused more on the start techniques on this new start block. The aim of this study is to summarize the current literature regarding the kinematics research progress of swimming start on this new start block and find the proper swim-start to optimize the swimming performance. The aim of this study is to provide insight into the improvement of swimming performance on the new start block by kinematics view for coaches and athletes. Results suggest that the KS is superior to the TS and GS. With the introduction of the OSB11 starting plate, swimmers need to quickly modify and adjust their techniques to take advantage of the new swimming start plate during normal training. The swimmers should not only enhance their speed training and speed training methods but also strengthen the core and lower limb strength to obtain the best take-off forces and horizontal velocity.